DEVELOPING PLAY AS PEDAGOGY IN LOWER PRIMARY CLASSROOM - Lee Jun Chien (Siliwangi University, 2017)
In recent years, there is extensive evidence on learning through play, however, there has been less evidence in teaching through play. This paper will begin by examining play elements in the Strategies for English Language Learning and Reading (STELLAR) Programme in Singapore. It will then proceed to discuss on developing a pedagogy of play for lower primary classroom. To link play and pedagogy, understanding on the unique purposes and nature of play in education settings as well as the role of adults in planning and involving in various activities are essential. This paper will address three themes: the influence of STELLAR curriculum in Singapore, critical issues on play in theory and in practice, and future directions in research. STELLAR, as one of the initiatives imparting primary school does influence not only pedagogical and classroom practices, but also the universal concern for examinations. Teachers, on the other hand, having role on providing good quality play, enable students to explore, adventure and engage in fun-filled activities must also try to adapt with the intention to mesh with MOE policies. Hence, it is important to support and equip teachers and with designated and professional knowledge and expertise in play as pedagogy.